Improving Surveillance Across the CEMAC Region - Iossifov, Plamen (IMF Working Papers; Working Paper, 2009)
In this paper, we consider the design of the surveillance, and, in particular, the fiscal criteria in the Central African Economic and Monetary Community (CEMAC) with the view to ensuring they are consistent with internal and external sustainability. This consistency is important within a monetary union because fiscal policy is the primary instrument through which national governments can influence macroeconomic performance. We comment on how surveillance might be improved by broadening the region's current criteria through alternative fiscal indicators, some focus on the scope and nature of external shocks, and attention to the consistency of policies in assuring the viability of the union and its fixed exchange rate regime.